Hip depth and performance in 400 m front crawl test - Correia, A.; Feitosa, W. G.; Franken, M.; Matos, C.; Castro, F. A. de S. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
One of the factors that can limit speed and performance in swimming is the body position in water. Considering hydrodynamic drag, it is expected that hip depth (Dh) position will compromise swim speed and performance, especially in the front crawl stroke. Thus, the purpose of this study was to describe Dh in swimmers of different performance levels throughout a maximal 400 m front crawl test (T400). Six competitive male swimmers (divided in two equal groups, G1: upper performance and G2: lower performance) performed a T400 in a 25 m swimming pool. Vertical position of the hip (landmarks were manually digitized) in relation to the surface of the water was analyzed by means of 3D cinemetry. The null hip roll angle was controlled (horizontal rolling position, hip parallel to the surface of the water) and Dh was identified in this body position. Average Dh values were calculated. The T400 performance and its average swimming speed were also obtained. Performance in the T400, speed and Dh in G1 and G2 performance groups were, respectively, 275.67 ± 3.79 s and 339.67 ± 28.28 s ; 1.44 ± 0.02 m/s and 1.18 ± 0.08 m/s; and 15.7 ± 1.2 cm and 19.0 ± 0 cm. G1 had 23 ± 12% better performance than G2 and were 22 ± 9% faster than G2 . Dh was 22 ± 9% deeper in G2. This is an objective result in regards to the best swimming technique, drag, and consequent performance in front crawl.